Road safety survey 1997 - Swedish Road Administration (Swedish Transport Administration, 2014)
This is the 17th study in a series of annual surveys on road safety conducted since 1981. The study is conducted by Statistics Sweden on behalf of the Swedish National Road Administration, which had the overall responsibility for road safety in Sweden in 1997. Today the study is conducted on behalf of the Swedish Transport Administration.

The study aims to identify and analyse traffic safety statistics. This is done by a written questionnaire directed to a stratified sample of the population. The study from 1997 had a 75,4 percent response rate and a sample of 9 730 randomly selected people aged between 15 and 84 years. Since 1985 the age group -75 to 84 returns with four to five years.

The questions in the study include, for example, traffic behaviour and traffic patterns; attitudes to road safety and traffic rules, the relation between alcohol and traffic and child safety in traffic. Both motor traffic, bicycle and foot traffic is concerned. A total of 24 questions are used, including descriptive questions, estimation questions and attitude questions.

Purpose:

The survey aims to identify and analyse traffic safety statistics.

Detta är den sjuttonde studien i en serie av årliga undersökningar om trafiksäkerhet, som genomförts sedan 1981. Studien har utförts av Statistiska centralbyrån på uppdrag av Vägverket, som 1997 hade det övergripande ansvaret för trafiksäkerheten i Sverige. Idag utförs studien på uppdrag av Trafikverket.

Undersökningen syftar till att ta fram och analysera trafiksäkerhetsstatistik. Detta görs med en skriftlig enkät riktad till ett stratifierat urval av Sveriges befolkning. För studien 1997 var svarsfrekvensen 75,4 procent och urvalet 9 730 slumpmässigt utvalda personer i åldrarna 15 till 84 år. Åldersgruppen -75 till 84 år har regelbundet återkommit med fyra till fem års mellanrum i undersökningsserien.

Frågorna i studien behandlar bland annat trafikbeteende och trafikvanor, både hos sig själv och andra, inställning till trafiksäkerhet och trafikregler, relationen mellan alkohol och trafik samt barns säkerhet i trafiken. Både motortrafik, cykel och gångtrafik berörs. Totalt används 24 stycken frågor som består bland annat av beskrivande frågor, skattningsfrågor och attitydfrågor.

Syfte:

Syftet med studien är att ta fram och analysera trafiksäkerhetsstatistik.
Trafiksäkerhetsenkäten 1997
TS-enkäten 1997
Keywords: drinking behaviour; alkoholvanor; road traffic; vägtrafik; speed limits; fartgräns; road accidents; trafikolyckor; road safety; trafiksäkerhet; child safety; barnsäkerhet; traffic regulations; trafikbestämmelse; accidents; olyckor; traffic; trafik; road users; vägtrafikanter; velocity; hastighet; public health risks; hälsorisker; vehicle restraint systems; bilens inre säkerhet; traffic offences; trafikförseelse; Legislation and legal systems; Lagstiftning och rättssystem; Children; Barn; TRANSPORT AND TRAVEL; TRANSPORT OCH RESOR; Social Sciences; Samhällsvetenskap